Reducing the Risk of Food Vulnerability Due to Drought Through the Utilization of Food Vulnerability Atlas in Timor Tengah Selatan Regency - Nursalam, Nursalam (Iapa Proceedings Conference, 2024)
Disaster risk reduction is an effective disaster management paradigm in dealing with various disasters, including food insecurity disasters. One important instrument in reducing the risk of food insecurity disasters is a food vulnerability atlas owned by a government local. The method used is a qualitative method by relying on local government food vulnerability atlas documents. Based on the research results, it is known that 41 villages (14.74%) of the 278 villages throughout the Timor Tengah Selatan (TTS) regency are villages that are very vulnerable to food insecurity. Based on the results of the food vulnerability atlas, it can also be seen the regional government's strategy in overcoming highly vulnerable areas, namely through a program to increase food provision in non-production center areas by optimizing local food resources. This study also recommends that local governments increase basic infrastructure development programs (roads and clean water) in food-vulnerable areas.